A Study on Optimize Skip Stop Service Using Genetic Algorithm in Selected Indian Railway Division - Sengupta, Soumya; Neogi, Amartya (International Journal of Computer Sciences and Engineering, 2025)
Railway authorities aim to provide transportation service to the customer in a safe as well as effective and efficient manner. The main constraints forcing them to regulate their service are the limitation of resources. This paper found the optimal coordination of stopping stations that can increase and improve overall benefits of skip stop service. A skip stop pattern must find an optimal balance between faster passenger travel time and lower service frequencies at each station. The main objective is to optimize passenger travel time with maintaining railway and infrastructural behavior.